Time to Loss of Consciousness and Its Relation to Behavior in Slaughter Pigs during Stunning with 80 or 95% Carbon Dioxide - Verhoeven, Merel; Gerritzen, Marien; Velarde, Antonio; Hellebrekers, Ludo; Kemp, Bas (Frontiers in Veterinary Science, 2016)
Exposure to CO2 at high concentration is a much debated stunning method in pigs. Pigs respond aversively to high concentrations of CO2 and there is uncertainty about what behaviors occur before and after loss of consciousness. The aim was to assess timing of unconsciousness in pigs during exposure to high concentrations of CO2 based upon changes in EEG activity and the relation with the behaviors sniffing, retreat- and escape attempts, lateral head movements, jumping, muscular contractions, loss of posture, and gasping. Pigs (108 ± 9 kg) were randomly assigned to 80% CO2 (80C, n=24) or 95% CO2 (95C, n=24). The time at which the gondola started descending into the well pre-filled with 80C or 95C was marked as T=0. The CO2 exposure lasted 346s after which the corneal reflex and breathing were assessed for one minute. Visual assessment of changes in the amplitude and frequency of EEG traces after T=0 was used to determine loss of consciousness. Time to loss of consciousness was longer in 80C pigs (47 ± 6s) than in 95C pigs (33 ± 7s). Time to an iso-electric EEG was similar in 80C pigs (75 ± 23s) and 95C pigs (64 ± 32s). When pigs descended into the well, the earlier entry of 95C pigs into high CO2 atmosphere rather than the concentration of CO2 by itself affected the latency of behavioural responses and decreasing brain activity. During exposure to the gas, 80C and 95C pigs exhibited sniffing, retreat attempts, lateral head movements, jumping and gasping before loss of consciousness. 95C pigs exhibited all these behaviors on average earlier than 80C pigs after T=0. But the interval between onset of these behaviors and loss of consciousness and the duration of these behaviors, except gasping, was similar for both treatments. Loss of posture was on average observed in both groups 10s before EEG-based loss of consciousness. Furthermore, 88% of 80C pigs and 94% of 95C pigs demonstrated muscular contractions before loss of consciousness. The findings provide little reason to conclude on a behavioral basis that these atmospheres are greatly different in their impact on pig welfare.